Functional Outcome of Elderly Patients Treated for Odontoid Fracture: A Multicenter Study. Issue 13 (1st July 2019) - De Bonis, Pasquale; Iaccarino, Corrado; Musio, Antonio; Martucci, Antonio; De Iure, Federico; Donati, Roberto; Cultrera, Francesco; Tosatto, Luigino; Servadei, Franco; Alesi, Domenico; Cavallo, Michele Alessandro; Ghadirpour, Reza; et al.
Abstract : Study Design: Retrospective multicenter study. Objective: Analysis of impact of conservative and surgical treatments on functional outcome of geriatric odontoid fractures. Summary of Background Data: Treatment of odontoid fractures in aged population is still debatable. Methods: One hundred fourty-seven consecutive odontoid fractures in elderly patients were classified according to Anderson-D'Alonzo and Roy-Camille classifications. Philadelphia type collar was always positioned and kept as a treatment whenever acceptable. Halo-vest, anterior screw fixation, C1–C2 posterior arthrodesis, and occipito-cervical fixation were the other treatments adopted. Conservative or surgical treatment strategy was more significantly influenced by antero-posterior displacement (< or >5 mm) and by surgeon decision. On admission ASA, modified Rankin scale (mRS-pre) and Charlson Comorbidity Index (CCI) were assessed. Modified Rankin scale (mRS-post), Neck Disability Index (NDI), and Smiley Webster Pain Scale (SWPS) were administered 12 to 15 months after treatment to estimate functional outcome in terms of general disability, neck-related disability, and ability to return to work/former activity. Risk of treatment crossover was calculated considering factors affecting outcome. Fracture healing process in terms of fusion-stability, no fusion-stability, no fusion-no stability was evaluated at 12 months through a cervical computed tomography (CT) scan. Dynamic cervical spine x-rays were obtained whether necessary. No fusion-stability was considered an adequate treatment goal in our geriatric population. Chi square/Fisher exact test and logistic regression were performed for statistical anal. Results: Overall 67 patients were treated conservatively whereas 80 underwent surgery. Collar was adopted in 45 patients, while anterior odontoid fixation and C1–C2 posterior arthrodesis were preferred for 30 patients each. 79.8% of patients showed good outcomes according to NDI. No significant differences were observed between patients of 65 to 79 years and more than or equal to 80 years ( P = 0.81). CCI greatly correlated with mRS-post, with higher indexes in 68.8% of cases characterized by good outcomes ( P = 0.05). mRS-pre correlated with NDI ( P < 0.000001) and mRS-post ( P = 0.04). CCI, mRS-pre, and surgery were associated with worse NDI, while both C1–C2 posterior arthrodesis and occipito-cervical stabilization were associated with worse mRS-post, respectively in 40% and 30% of cases. Younger patients had a higher risk of treatment crossover. Conclusion: mRS-pre and CCI provided two independent predictive values respectively for functional outcome and post-treatment disability. Compared with conservative immobilizations, surgery revealed no advantages in the elderly in terms of functional outcome. Level of Evidence: 3 Abstract : Functional outcome of elderly patients treated for odontoid fracture is strictly related to their pre-injury level of function and comorbidity. Compared with conservative external immobilizations, surgery revealed no advantages in the elderly in terms of functional outcome.